Phase 2 Trial of Paclitaxel, 13-cis Retinoic Acid, and Interferon Alfa-2b in the Treatment of Advanced Stage or Recurrent Cervical Cancer. Issue 9 (1st November 2014) - Song, Mihae; DiPaola, Robert S.; Cracchiolo, Bernadette M.; Gibbon, Darlene G.; Hellmann, Mira; Nieves-Neira, Wilberto; Vaidya, Ami; Wagreich, Allison R.; Shih, Weichung J.; Rodriguez-Rodriguez, Lorna
Abstract : Objective: Overexpression of bcl-2 is a mechanism of drug resistance in cervical cancer. Agents that down-regulate bcl-2 may decrease tumor cell threshold and sensitize tumor cells to chemotherapy. The objective of this multi-institutional phase 2 trial was to evaluate the efficacy and toxicity of paclitaxel and bcl-2 modulators (13-cis retinoic acid and interferon alfa-2b) in patients with advanced-stage or recurrent cervical cancer. Materials and Methods: Patients had biopsy-proven metastatic, first relapse, or persistent cervical cancer with no prior chemotherapy except for chemosensitizing agents. The treatment consisted of oral 13-cis retinoic acid, 1 mg/kg, and subcutaneous interferon alfa-2b, 6 mU/m 2, days 1 to 4, and intravenous paclitaxel, 175 mg/m 2, day 4 until disease progression or adverse events prohibited treatment. The primary endpoint was overall response rate. Results: Thirty-three patients were enrolled between March 2001 and June 2009. Thirty-one patients were eligible for evaluation of treatment response. Twenty-seven patients (82%) received prior concurrent chemoradiation or radiotherapy alone before study enrollment. The overall response rate was 30% (6 complete responses and 4 partial responses). Furthermore, 7 patients (21%) had stable disease. Grade 3 or 4 adverse events included neutropenia (n =16 [48%]), febrile neutropenia (n = 1 [3%]), and anemia (n = 1 [3%]). There were no treatment-related deaths. The median progression-free survival was 3.4 months (95% confidence interval, 2.0–7.4 months), and overall survival was 11.2 months (95% confidence interval, 7.5–26.2 months). Of 6 patients with complete responses, 5 patients survived more than 2 years. Conclusions: Combination therapy with paclitaxel, 13-cis retinoic acid, and interferon alfa-2b is feasible and safe in treating patients with advanced and recurrent cervical cancer.